2020
DOI: 10.21203/rs.3.rs-131480/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis of messenger RNA and long noncoding RNA related to different developmental stages of tail adipose tissues of sunite sheep

Abstract: Background: Sunite sheep are a fat-tailed sheep species with a low percentage of intramuscular fat and good quality lean meat, and their tail fat can be used as a source of dietary fat by humans. To understand the potential regulatory mechanism of different growth stages of tail fat in Sunite sheep, we performed high-throughput RNA sequencing to characterize the long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression profiles of the sheep tail fat at the age of 6 months, 18 months, and 30 months.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition ( Ahbara et al, 2018 ; Amane et al, 2020 ; Baazaoui et al, 2021 ; Bakhtiarizadeh & Alamouti, 2020 ; Dong et al, 2020 ; Han et al, 2021 ; Li et al, 2018a ; Mastrangelo et al, 2019a ; Mastrangelo et al, 2019b ; Moioli, Pilla & Ciani, 2015 ; Moradi et al, 2012 ; Wei et al, 2015 ; Xu et al, 2017 ; Yuan et al, 2017 ; Zhang et al, 2019 ; Zhao et al, 2020 ; Zhi et al, 2018 ; Zhu et al, 2016 ). Previous studies suggested that microRNAs ( Miao et al, 2015a ; Pan et al, 2018 ), lncRNAs ( Bakhtiarizadeh & Salami, 2019 ; He et al, 2020 ) and mRNAs ( Bakhtiarizadeh et al, 2019 ; Kang et al, 2017a ; Miao et al, 2015b ; Wang et al, 2014 ) may regulate tail fat deposition in sheep. These results contribute to understanding the underlying mechanisms of fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition ( Ahbara et al, 2018 ; Amane et al, 2020 ; Baazaoui et al, 2021 ; Bakhtiarizadeh & Alamouti, 2020 ; Dong et al, 2020 ; Han et al, 2021 ; Li et al, 2018a ; Mastrangelo et al, 2019a ; Mastrangelo et al, 2019b ; Moioli, Pilla & Ciani, 2015 ; Moradi et al, 2012 ; Wei et al, 2015 ; Xu et al, 2017 ; Yuan et al, 2017 ; Zhang et al, 2019 ; Zhao et al, 2020 ; Zhi et al, 2018 ; Zhu et al, 2016 ). Previous studies suggested that microRNAs ( Miao et al, 2015a ; Pan et al, 2018 ), lncRNAs ( Bakhtiarizadeh & Salami, 2019 ; He et al, 2020 ) and mRNAs ( Bakhtiarizadeh et al, 2019 ; Kang et al, 2017a ; Miao et al, 2015b ; Wang et al, 2014 ) may regulate tail fat deposition in sheep. These results contribute to understanding the underlying mechanisms of fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition (Ahbara et al 2018;Amane et al 2020;Baazaoui et al 2021;Bakhtiarizadeh & Alamouti 2020;Dong et al 2020;Han et al 2021;Li et al 2018a;Mastrangelo et al 2019a;Mastrangelo et al 2019b;Moioli et al 2015;Moradi et al 2012;Wei et al 2015;Xu et al 2017;Yuan et al 2017;Zhang et al 2019;Zhao et al 2020;Zhi et al 2018;Zhu et al 2016). Previous studies suggested that microRNAs (Miao et al 2015a;Pan et al 2018), lncRNAs He et al 2020) and mRNAs Kang et al 2017a;Miao et al 2015b;Wang et al 2014) may regulate tail fat deposition in sheep. These results contribute to understanding the underlying mechanisms of fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition (Ahbara et al 2018;Amane et al 2020;Baazaoui et al 2021;Bakhtiarizadeh & Alamouti 2020;Dong et al 2020;Han et al 2021;Li et al 2018a;Mastrangelo et al 2019a;Mastrangelo et al 2019b;Moioli et al 2015;Moradi et al 2012;Wei et al 2015;Xu et al 2017;Yuan et al 2017;Zhang et al 2019;Zhao et al 2020;Zhi et al 2018;Zhu et al 2016). Previous studies suggested that microRNAs (Miao et al 2015a;Pan et al 2018), lncRNAs He et al 2020) and mRNAs Kang et al 2017a;Miao et al 2015b;Wang et al 2014) may regulate tail fat deposition in sheep. These results contribute to understanding the underlying mechanisms of fat deposition.…”
Section: Introductionmentioning
confidence: 99%